Literature Study Of Problem-Based Learning Models On Mathematics Learning - Pujihastuti, Wiwin Retno (Universitas Sebelas Maret, 2022)
The purpose of this study was to examine the literature on problem-based learning models based on the problem of the basic concept of multiplication. Data collection was carried out by collecting related books and journals to be read and studied. After the data is collected, testing and comparison of the data found is carried out. The data analysis technique was carried out qualitatively by quoting the appropriate opinions. The results of the research show that the problem-based learning model is a very good model to use in learning mathematics. This can be seen from the many learning theories that support the problem-based learning model in learning and show significant results.